Assessment of lignite upgrade and hydrogen evolution via electrolysis. (1st February 2022) - Lyu, Xiang; Hu, Junyi
Graphical abstract: Highlights: A modified coal electrolytic cell was designed and built with high performance. 20.9% fixed carbon and 8.15% heating value increase in lignite after electrolysis. 71.5% ash and 39.6% mercury are removed in lignite after electrolysis. The Faradaic efficiency of H2 evolution reaches 99% via lignite electrolysis. A novel method for H2 evolution and lignite upgrade is developed. Abstract: Lignite, considered as the lowest-rank coal, accounts for 45% of the total coal resources worldwide, and its low carbon and high ash contents limit its large-scale application. In order to upgrade lignite effectively, a modified coal electrolytic cell (MCEC) was designed, built, and then evaluated for lignite upgrade and hydrogen production through electrolysis, and the operating conditions were optimized. The results show that the performance of the MCEC outperformed the previous coal electrolytic cell (CEC). The operating temperature and iron concentration significantly impact the average current density per milligram of catalyst (ACDMC). The content of dry fixed carbon and heating value increased by 20.9% (wt%) and 8.15%, respectively, in electrolyzed lignite compared with raw lignite. Besides, 71.5% ash and 39.6% mercury were removed from raw lignite after electrolysis, which is the first report. The Faradaic efficiency (FE) for hydrogen evolution reached 99% using MCEC. In addition, the analysis of spectroscopy methods (SEM, EDX, FTIR, and XRD) revealed that the lignite particles were cracked; the oxygen-containing functional groups increased; the minerals of quartz and hematite formed on the surface of lignite particles after electrolysis. The facts indicate that electrolysis of lignite is a competitive approach for lignite upgrade and hydrogen production.